The war in the Pacific from Pearl Harbor to Tokyo Bay - Gailey, Harry A. (Presidio, 1997)
A widely praised Pacific War historian--and author of The Liberation of Guam--draws on his extensive knowledge and new scholarship to shape this detailed treatment of the war against Japan, carefully examining the close interaction between naval, air, and land forces in every military operation.